Magnetic FieldPolarity Sensor by Using Trapped Magnetic Flux in Y-Ba-Cu-O Ceramic Superoconductor. - Wisut Titiroongruang; Sang Heon Lee; Yukio Akiba; Tateki Kurosu; Masamori Iida (My University, 1995)
The relation between electrical properties of Y-Ba-Cu-O ceramic superconductor and externally applied magnetic field has been studied. The electrical resistance of the superconductor increased by the application of the external magnetic field. But the increase continues even after the removal of the magnetic field. The reason is as follows; the magnetic flux due to the external magnetic field penetrates through the supercondutor and the penetrated magnetic flux is trapped after the removal of the magnetic field. Some portion of the superconductor changes to the normal state by the trapped magnetic flux. The appearance of the normal state yields to the increase in the electrical resistance Electrical characteristics of the superconductor with trapped magnetic fluxes are extremely sensitive to the external magnetic field and show the different responses which depend on the direction of the magnetic field. Considering these properties of the superconductor with trapped magnetic fluxes, a magnetic sensor is fabricated. This sensor is able to detect simultaneously both the intensity and the direction of the magnetic field. The sensitivity of the sensor is less than 10-4T.
Keywords: Superdiamagnetism; Magnetic confinement fusion research